2005
DOI: 10.1021/cg0495678
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Single Crystal Growth of PbMoO4

Abstract: The synthesis of polycrystalline PbMoO4 material suitable for use as the starting charge for crystal growth was investigated employing a solid-state sintering method. The solidification behavior of the material was studied by the differential thermal analysis (DTA) technique, with an aim to model the growth by the Czochralski technique. Actual crystal growth runs were carried out to validate the modeling and identify conditions that yield good quality crystals. The results show that large changes in melt stoic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 4 publications
2
20
0
Order By: Relevance
“…The problem of crystal cracking was investigated in some detail by Bonner and Zydzik [2] and related it to anisotropic thermal contraction of LMO. The subsequent experimental results reported by Takano et al [3], Sabharwal et al [4] and the results of numerical analysis by Miyazaki et al [5] have been found to be in agreement with conclusion of Bonner and Zyzdik. However, it should be mentioned that these results do not comply with the experimental results on sub-grain distribution in LMO, single crystals reported by a number of research groups [3,6,7].…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…The problem of crystal cracking was investigated in some detail by Bonner and Zydzik [2] and related it to anisotropic thermal contraction of LMO. The subsequent experimental results reported by Takano et al [3], Sabharwal et al [4] and the results of numerical analysis by Miyazaki et al [5] have been found to be in agreement with conclusion of Bonner and Zyzdik. However, it should be mentioned that these results do not comply with the experimental results on sub-grain distribution in LMO, single crystals reported by a number of research groups [3,6,7].…”
Section: Introductionsupporting
confidence: 85%
“…The melt grown crystals have also been reported to easily crack either during growth or on subsequent handling. In a recent communication, we have reported the growth of LMO crystals free from the presence of macroscopic defects [4]. In that study, the crystal growth parameters and the growth direction were identified which yielded crack-free ingots.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The non-stoichiometry manifests in different ways by influencing the optical and other physical properties of the crystal or it may promote the incorporation of impurities during crystal growth (Sabharwal et al 1996(Sabharwal et al , 2006Sabharwal andSangeeta 1999, 2008). The colouration of LGO-2 is related to Pb deficiency as borne out by the present measurements.…”
Section: Discussionmentioning
confidence: 99%
“…A major problem faced with the growth of LMO crystals is the occurrence of non-stoichiometry, which arises due to the excessive vapour pressure of MoO 3 over PbO at elevated temperatures. The preferential and uncontrolled depletion of MoO 3 during growth gives rise to colouration and cracking of the as-grown crystals (Zeng 1996;Bochkova et al 2003;Sabharwal et al 2006;Sangeeta et al 2006;Tyagi et al 2008). The presence of defects arising as a consequence of the stoichiometric deviations is also found to influence the crystal ionic conductivity (Neiman et al 1984).…”
Section: Introductionmentioning
confidence: 99%